Minister Receives Doctorate - New Straits Times, (2008)
Minister inthe Prime Minister's Department Datuk Seri Dr Ahmad Zahid Hamidi was among 176 graduates who received their Phd at Universiti Putra Malaysia 32nd convocation here yesterday.